Akademia Lubrańskiego – chluba Poznania. W 500. rocznicę fundacji - Nowicki, Michał (Biuletyn Historii Wychowania, 2019)
1519 was a special year for the city of Poznań, owing to the foundation of a new school, the Lubrański Academy. It was the first school of humanities in Poland to follow the best models of Renaissance education and employed illustrious teachers like Krzysztof Hegendorfer and Benedykt Herbest. In the 16th century, the Academy was considered a rival of Krakow University; ultimately in the early 17th century, the Academy was affiliated with the University. As a result of the affiliation, the Poznań school enjoyed stability, a group of experienced teachers and a curriculum recognized by the society. The curriculum stood out in Poland by its inclusion of practical preparation for performing various political functions, especially in the field of law, and, as in other educational institutions, by preparing young people for cultural life in the country. Its relations with Krakow University also had drawbacks: during the Enlightenment reforms of the education system, the Lubrański Academy adopted a conservative and reactionary position. Despite this, the authorities managed to introduce several modern solutions, especially in the realm of teaching modern foreign languages.